Michelle Murphy with Mrs. Alfred Abram - Martin & Rita Rowe (photographic studio):::Creator::::::::::::
Photograph shows Michelle Murphy with a blindfold on, holding a stick, and standing in front of a Christmas tree pinata. Mrs. Alfred Abram is helping her and there is a group of children standing behind them.